Perencanaan dan Evaluasi User Interface untuk Aplikasi Tunanetra Berbasis Mobile Menggunakan Metode User Center Design dan QUIM Evaluation - Frobenius, Arvin Claudy (Jurusan Informatika Universitas Tanjungpura, 2021)
Blind people are identified as someone who has limited vision. Difficulty in navigation is one of the problems faced by blind people when doing daily activities, one of which is the use of smartphones. In the development of the current technological era, the use of smartphones is very important where smartphones have the benefit of being able to be used and carried easily anytime and anywhere. However, not all applications are easy to use both in appearance and experience for blind people, because of the limitations that blind people have, this is because they have not paid attention to the user interface and user experience of blind users. One of them is the Gablind mobile application, which is an Internet of Thing (IoT) based application that is integrated with special glasses for visually impaired persons, which are used by blind people to navigate when doing activities outside. At the development stage of the Gablind application, planning requires both the user interface and the user experience, so that the features in the application can be used properly by blind people. This research focuses on the user, namely applying the user-centred design (UCD) method and the method of identifying usability using the QUIM factor. Based on the evaluation analysis of this study, the overall average value of the QUIM factor is 81.3%, so it is categorized as good. The factors that score <= 80% and above are usefulness, universality, accessibility, trustfulness, and learnability. Meanwhile, there are also factors that need to be improved because the value is less than 70%, namely productivity and satisfaction.